2018
DOI: 10.1007/s12355-018-0595-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Soil CO2 Emission and Soil Attributes Under Contrasting Sugarcane Cultivars

Abstract: Agriculture is a great emission source of CO 2 into the atmosphere, contributing significantly to the greenhouse effect. Considering the hypothesis that there are differences in soil carbon dynamics due to the distinct physiological and morphological characteristics of sugarcane cultivars, the aim of this study was to characterize the short-term soil CO 2 emission associated with soil attributes in agricultural areas under cultivation of five sugarcane cultivars. The experiment was conducted in an area of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A recent study had reported that sugarcane crop cover and tillage at a minimum level forms a strong and efficient approach in mitigating the CO 2 emissions emitted from soil (Farhate et al, 2018). Moitinho et al (2018) had revealed that different sugarcane cultivars respond differently for soil CO 2 emissions and one must keep in mind that prior to planting of sugarcane as a management tool for mitigating GHGs emission, one must look for the cultivar to be planted.…”
Section: Effect Of Elevated Co 2 Concentration On Sugarcanementioning
confidence: 99%
“…A recent study had reported that sugarcane crop cover and tillage at a minimum level forms a strong and efficient approach in mitigating the CO 2 emissions emitted from soil (Farhate et al, 2018). Moitinho et al (2018) had revealed that different sugarcane cultivars respond differently for soil CO 2 emissions and one must keep in mind that prior to planting of sugarcane as a management tool for mitigating GHGs emission, one must look for the cultivar to be planted.…”
Section: Effect Of Elevated Co 2 Concentration On Sugarcanementioning
confidence: 99%